The expression \( 2712 \cdot 2714 \) can be rewritten using properties of exponents.
-
Using Exponent Properties: \[ 2712 \cdot 2714 = 27^{12} \cdot 27^{14} = 27^{12 + 14} = 27^{26} \]
-
Using Root Properties: The expression \( 27^{12} \cdot 27^{14} \) can also be expressed in radical form: \[ 27^{26} = \sqrt[4]{27^4} = \sqrt[3]{27^3} = 27^{3 \cdot \frac{26}{3}} = 27^{\frac{78}{3}} = 27^{26} \]
So, combining these, we can write:
\[ 2712 \cdot 2714 = 27^{26} \]
This is a simplified and rewritten form of the expression \( 2712 \cdot 2714 \).